Pengaruh Reward Stiker Keaktifan sebagai Penguatan Positif terhadap Motivasi Belajar Matematika Siswa Kelas VIII - Amalia, Nur; Baharuddin; Rosdiana (Papanda, 2025)
This study aims to determine the level of learning motivation of grade VIII.K through the provision of rewards in the form of activeness stickers as a form of positive reinforcement. Initial observations show that most students are not interested in learning mathematics, as evidenced by their low participation in answering questions, doing exercises, and discussing. This condition makes it difficult for teachers to encourage students to be more enthusiastic and motivated. This study uses the Classroom Action Research (PTK) method which adapts the Action research model by Kemmis & McTaggart. The subjects in this study were 32 students in class VIII.K. In collecting data, this study used the method of observation of learning activities and a mathematics learning motivation questionnaire using a research instrument in the form of a mathematics learning motivation questionnaire using a Likert scale. The data analysis technique used is descriptive analysis of qualitative and quantitative data. The results showed that the average student learning motivation went from 65 (sufficient category) in the pre-cycle, to 74 (high category) in the first cycle, and to 86 (very high category) in the second cycle. Thus, the provision of rewards in the form of activeness stickers as a form of positive reinforcement has been proven to increase the motivation to learn mathematics of students in class VIII.K SMP Negeri 2 Palu. This improvement shows that simple reward such as activeness stickers are able to be foster a sense of joy, be appreciated, and encourage to be more active in learning.